Um ADC-SAR em modo de corrente com número reduzido de células de memória - Falleiro, Fellipe Diogo (2018)
This work presents the development of an ADC-SAR in current mode with reduced amount of memory cells, regardless the conversion`s length. The fully recursive mode of operation implies increasing the sensitivity of the structure. Knowing this, we present some techniques capable of increasing the accuracy of the circuit even after considering the imprecisions caused by charge injections and mismatch. Some results are obtained by simulation and these are used to compare the proposed structure with other structures present in the current literature.